Chitosan and chitosan-co-poly(epsilon-caprolactone) grafted multiwalled carbon nanotube transducers for vapor sensing - Rana, Vijay Kumar; Akhtar, Shamim; Chatterjee, Sudipta; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Nanoscience and Nanotechnology, 2014)
Vapor sensitive transducer films consisting of chitosan grafted (CNT-CS) and chitosan-co-polycaprolactone grafted (CNT-CS-PCL) multiwalled carbon nanotubes were prepared using a spray layer-by-layer technique. The synthesized materials (CNT-CS and CNT-CS-PCL) were characterized by Fourier transform infrared spectroscopy, C-13 CP/MAS solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis. Both CNT-CS and CNT-CS-PCL transducers were analyzed for the response of volatile organic compounds and toluene vapors. The ranking of the relative resistance (A(r)) for both chitosan based transducers were as follows: toluene < chloroform < ethanol < methanol. The CNT transducer (CNT-CS) was correlated selectively with an exponential law to the inverse of Flory-Huggins interaction parameters, chi(12). Dosing the films on the interdigitated electrodes with methanol, ethanol, chloroform and toluene vapors increased the film resistance of CNT-CS but decreased the resistance of CNT-CS-PCL compared to that of the reported transducers.
Keywords: Biocompatibility; Chitosan; MWCNTs; Poly(epsilon-caprolactone); Vapour Sensing

Photo and pH dual stimuli-responsive block copolymer micelles with defined incorporation of o-nitrobenzyl units in poly(ε-caprolactone) ε-caprolactone) block for controlled release - Avhad, V. Shankarrao; Choudhari, Shakeb N.; Ambade, V. Ashootosh (European Polymer Journal, 2024)
A series of dual stimuli-responsive block copolymers with varying content of photocleavable o-nitrobenzyl (ONB) ester group pendent in the hydrophobic poly(epsilon-caprolactone) block and pH-cleavable acetal linkage at the junction with hydrophilic poly(ethylene glycol) block is synthesized. The hydrophobic block is a random copolymer synthesized by ring-opening copolymerization of epsilon-caprolactone and ONB-substituted epsilon-caprolactone containing varying compositions of the two monomers. Kinetics of polymerization shows that ONBfunctionalized monomer has lower reactivity than that of the unsubstituted monomer. The series of block copolymers shows self-assembly into well-defined spherical micelles of average size of 150-200 nm in aqueous solution. Photocleavage of ONB groups is studied by NMR and UV-vis spectroscopy, and its extent is determined. The two stimuli viz. . UV light and pH are used individually as well as simultaneously to study the controlled release of the encapsulated drug Camptothecin and the synergistic effect of the two stimuli is demonstrated. The effect of varying content of ONB groups is observed on drug release profile. MTT assay showed non-cytotoxic nature of the polymer. Cell uptake and photoinduced release of doxorubicin (DOX) from the micelles in MDAMB-231 cells is demonstrated.
Keywords: drug delivery; micelles; O-nitrobenzyl; pH-responsive; Photoresponsive; Poly(epsilon-caprolactone)